1940
DOI: 10.2307/1417630
|View full text |Cite
|
Sign up to set email alerts
|

Feral Man and Extreme Cases of Isolation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1942
1942
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…It is important to emphasize that the well‐documented negative impacts of deprivation on brain circuitry do not mean that excessive enrichment produces measurable enhancements in brain function. A small number of case reports exist in which neglected children with very little language experience in early childhood were given enriched language exposure in a protective environment (Curtiss, 1977; Itard, 1801/1932; Zingg, 1940). Longitudinal follow‐up studies of these children demonstrated that after several years of language exposure, they were unable to achieve adult‐level native language abilities.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…It is important to emphasize that the well‐documented negative impacts of deprivation on brain circuitry do not mean that excessive enrichment produces measurable enhancements in brain function. A small number of case reports exist in which neglected children with very little language experience in early childhood were given enriched language exposure in a protective environment (Curtiss, 1977; Itard, 1801/1932; Zingg, 1940). Longitudinal follow‐up studies of these children demonstrated that after several years of language exposure, they were unable to achieve adult‐level native language abilities.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…These stories propel anthropological imagination far beyond the idea of the “noble savage” that originated in Rousseau's Social Contract (Rousseau 1997) and past the once‐popular anthropological pursuit of “the savage in the state of nature” who would help us resolve which aspects of human social behavior are innate and which are acquired (cf. Volkmar and Klin 1993; Zingg 1940).…”
Section: Children With Autism and Animals In Myth And Historymentioning
confidence: 99%
“…A small number of case reports of children who were extremely neglected make up much of this literature. As a result of their neglect these children were provided very little language experience until later childhood when they were taken into protective custody and provided with enriched language exposure (Curtiss, 1977;Itard, 1932;Zingg, 1940). Longitudinal follow-up studies of these children demonstrated that, after several years of language exposure, they were unable to achieve language abilities of adult, native speakers.…”
Section: Late Onset Of First Language Learningmentioning
confidence: 99%